Rendahnya Minat Belajar Siswa Pendidikan Agama Kristen : Studi Kasus di SMPN 2 Sumbermanjing Wetan - Siani listio (DIDAKTIKOS: Jurnal Pendidikan Agama Kristen Duta Harapan, 2022)
AbstractOne of the successes in learning is the student’s interest and the teacher’s skill in delivering material.Students of SMPN 2 Sumbermanjing Wetan, Christian Religious Education class are assumed to be less interesed in Christian Religious study. This can be showed from their attitudes such as being lazy in doing assignment, not pay attention to the teacher who teaches, but talking to themselves with their friends, often having permission to the toilet, considering Christian religious lesson is not important, because these lessons are often obstained at home or at the church.The purpose of this research is to find out whether the students of SMPN 2 Sumbermanjing Wetan understand the meaning of interest in learning,  to know the condition of their interest in learning, and to find out the causes and solutions so that they can be interested in the subject of Christian Religious EducationThis research uses qualitative method with an intrinsic case study approach because the researcher wants to understand this case in all its specificity and simplicityThe results obstained from observations, interviews, and existing documents show that SMPN 2 students understand the meaning og interest in learning. The constraints come from students (less enthusiastic, unstable). The other constraints are religion classroom with capacity of 30 filled more than 30 .There  is no fan in the class, the hot air  make them discomfort.Lesson conducted at noon  between 10.50 – 12.50 and the lack of supporting facilities such LCD which are limited , so the teacher is not always able to use this facility            To overcome this situation , teacher creativity is needed in in teaching. Class can divided in groups , giving group assigments that can be done outside the classroom, still encouraging or give motivation to the students, providing guidance or conseling outside of teaching hours.  The coorperation among students, teachers, and school principal ai also needed and spiritual guidance teacher in spurring student interest in learning